Formation of chromium containing impurities in (La, Sr)MnO3 solid-oxide-fuel-cell cathodes under stack operating conditions and its effect on performance. Issue 8 (June 2016) - Roehrens, D.; Neumann, A.; Beez, A.; Vinke, I.C.; de Haart, L.G.J.; Menzler, N.H.
Abstract: In this study, we present an investigation of the chromium-related electrical performance degradation of anode-supported SOFCs with a LSM/YSZ composite cathode. A traditional ferritic interconnect steel with high chromium content is established as the primary chromium source and chromium poisoning of the cathode is carried out at relevant SOFC operating conditions. The prolonged influence of the gaseous chromium species on the cell performance and cathode microstructure under constant current conditions was examined quantitatively. Physical deposition of chromium(III) compounds (mainly spinel-type (Cr, Mn)3 O4 phases) was observed at the electrochemically active region adjacent to the electrolyte only under realistic constant current conditions. The microstructural degradation associated with the formation of secondary phases correlated directly with the performance degradation, the effective chromium partial pressure and the current density. Furthermore, the influence of the presence of a number of protecting layers on the interconnect steel was evaluated with regard to the cathode poisoning. It was shown that chromium-induced degradation was reduced drastically when an additional manganese reservoir layer and a Cr getter layer were applied.